The impact of strategic Facilities Management on the Employee Value Proposition - Mthiyane, Sandile (Department of Construction Economics and Management, 2019)
Facilities Management (FM) has and continues to evolve strongly as a strategic function in many organisation. Many organisations have also recognised the importance of human capital for the success of their operations. This is why the concept of Employee Value Proposition (EVP) is growing in popularity and is becoming one of the main focuses especially in human capital management spheres. Whilst there are many factors that contribute to the EVP, strategic FM has not been one of the focus areas. Although strategic FM has had a focus on user satisfaction as well as the usability of facilities, the focus of research to date has not necessarily been directed to EVP. Hence, this study explores the impact of strategic FM on employee value proposition. It explores this through quantitative and qualitative research means in a chosen case study of an organisation where strategic FM has been and still in the process of being implemented. The research establishes employee’s opinions on the importance of their work environment; whether their workspace support their effectiveness; whether their workspace provides flexibility for collaborations and teamwork; and other factors related to employee satisfaction. The findings of the study indicate that strategic FM does have an impact on employee value proposition. There are also indications that employees believe that FM services play a role in employee satisfaction which may lead to employee retention as well as employee recruitment which are two of the identified factors of employee value proposition.